Influência do comprimento do ninho-armadilha na seleção das cavidades para nidificação, na mortalidade da prole e na razão sexual de abelhas solitárias (Hymenoptera: Apidae) - Santos, Claudia Oliveira dos (2013)
This study aimed to investigate the acceptance of cavities with different lengths for nesting and the cavity size effects on the sex ratio and offspring mortality of solitary bees in two agricultural areas in Feira de Santana, Brazil. The samplings were carried out monthly, during 12 months, using trap-nesting (=NA) length 5, 10, 15 and 20 cm. A total of 124 nests, 591 building cells, and 479 emerging imago were sampled. There was a higher number of nesting in area I (n=86) than in area II (n=38). Centris analis Fabricius 1804, Centris tarsata Smith, 1874, and two Megachile species nested in área I, being C. analis the specie with highest number of established nest (n=72, 83.7%), while other species had low nesting frequency (4%) and a higher bee richness, with six species occupying the trap-nesting. Tetrapedia diversipes Klug, 1810, established highest number of nest (n=29, 76.3%). Species used different NA size in both areas. In the area I, they nesting with higher frequency in NA with 10 cm (38%) and 15 cm (38%), while in the area II, there was cavity occupation with 20 cm (50%). Bees nested in most part of the year, except in months of autumn-winter, between April and August, when the bee nesting frequency was reduced or the activity was suspended. The natural enemies that emerged from the nests were species of Hymenoptera Coelioxoides sp, Mesocheira bicolor Fabricius, 1804, and a species of Chrysididae. The mortality rate by unknown reason in the areas I and II was 21.4% and 13.5% respectively, with higher incidence recorded to Centris analis. There was a higher mortality in smallest nests (5 cm) and there was no difference among the cavities with 10, 15, and 20 cm.